Math
posted by Lucy .
Hi, I need a little help with solving this question for c:
(2c1)^3=4c^21
I did this already:
(2c1)^3(4c^21)=0
(2c1)^3(2c+1)(2c1)=0
But I need help with the next steps... Thank you!

(2c1)^3(2c+1)(2c1)=0
good so far, now take out a common factor
(2c1)[(2c1)^2  (2c+1)] = 0 expand and simplify to
(2c1)(4c^2  6c) = 0
(2c1)(c)(4c6) = 0
c = 1/2 or c = 0 or c = 3/2
Respond to this Question
Similar Questions

Algebra again
I don't understand how to do this problems: Solve for the variable r, C=2PIr (PI is the pi symbol thing then r is next to it) and this problem solve for the variable l, S=B+1/2Pl I know this is the same question, but I somewhat understand … 
Algebra
I was given an answer to a question but what I really need are the steps to get there as I have other questions I need to answer the same way. Solve the equation w=Cr^2 for r I was given r=C/w This equation is meant to figure out … 
Math
Hi...i asked a question about 45 minuets ago, and i have been working at it still. I still havn't gotten an anwser! Could somebody please help me! The question is, "this staircase has 3 steps (their are 6 blocks lined up as a staircase) … 
chemistry
i need steps of solving this question Balance the oxidation reduction equation in electron ion / half reaction please best regards 
Algebra
Simplify the complex rational expression 3/(x+5)+ 6/(x+3) ÷ (3x+13)/(x^2+8x+15) (please show steps i already know the answer i need to know the steps) 
math
17x – 42 = 39 i need to show the steps for solving this equation 
Trig
The next two steps in solving this trig identity question are ? 
Math
Solve the following equation u+2=4 The question for me is how do I solve these types of problem. I already know that u=2, but I need to know the steps to get to the answer. Thanks, Kaai97 
Math
Please what are the steps to solving this problem? 
Math
I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 − …